SOIL-WATER COUPLED ANALYSIS OF LOW LAND WIDESPREAD SUBSIDENCE DUE TO DEWATERING - K. Kaneda; H. Yamazaki (International Association of Lowland Technology, 2009)
A series of numerical simulations of land subsidence due to dewatering were performed based on the soilwater coupled finite deformation analysis using the SYS Cam-Clay model under plane-strain conditions. The simulations showed that after land subsidence, the ground may be fragile in the event of additional loading due to disturbance of the soil structure. Ground settlement occurs with cyclic variation in ground water level, assumed to be seasonal, due to a history of water level change from extraction. Such behavior is the result of soil disturbance that occurs due to decay of the soil structure, resulting in the softening of soils through plastic volume compression.